2004
DOI: 10.1149/1.1782141
|View full text |Cite
|
Sign up to set email alerts
|

Anode Supported Single Chamber Solid Oxide Fuel Cell in CH[sub 4]-Air Mixture

Abstract: In this study, yttrium-stabilized zirconia ͑YSZ͒ thin films 1-2 m thick electrolyte have been prepared using NiO-YSZ anode as substrates. Fuel cell test was conducted with the single chamber configuration in methane-air gas mixture using (La,Sr)(Co,Fe)O 3 ͑LSCF͒ as the cathode. Test results showed that the open-circuit voltage to be Ͼ0.8 V, with power density as high as 0.12 W cm Ϫ2 . It was also shown that gas flow rate has a large influence on the performance of the fuel cell, which indicates the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 10 publications
6
49
0
Order By: Relevance
“…Fuel utilization and cell efficiency of real SC-SOFC systems, however, are significantly lower than the ones predicted by Demin et al Anode-supported SC-SOFCs showed fuel utilization ranging from approximately 1% [88] to 2.4% [28] and an efficiency of about 1% [25]. For a fully-porous SC-SOFC, the fuel utilization was estimated to be 4-8% [87].…”
Section: Fuel Utilization and Fuel Cell Efficiencymentioning
confidence: 77%
See 3 more Smart Citations
“…Fuel utilization and cell efficiency of real SC-SOFC systems, however, are significantly lower than the ones predicted by Demin et al Anode-supported SC-SOFCs showed fuel utilization ranging from approximately 1% [88] to 2.4% [28] and an efficiency of about 1% [25]. For a fully-porous SC-SOFC, the fuel utilization was estimated to be 4-8% [87].…”
Section: Fuel Utilization and Fuel Cell Efficiencymentioning
confidence: 77%
“…Due to the use of a gas mixture, novel cell configurations such as fully porous and single-face SC-SOFCs with coplanar electrodes become possible that could not work under conventional, dual-chamber operating conditions. Moreover, the exothermic fuel oxidation reactions over the SC-SOFC electrode can cause a rise of the effective cell temperature by up to 100 °C [26][27][28], allowing lower operating temperatures and rapid start-ups. This heat release can lead to higher power densities in SC-SOFCs than in dual-chamber SOFCs at nominally lower furnace temperatures.…”
Section: Advantages Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The 25 m thick combustion layer mimics the reactor entrance, where an extremely rapid variation of temperature, velocity, and transport coefficients occurs. 5 The heat release in this layer not only provides the heat for the endothermic steam reformation, 2 but also leads to a significant temperature rise, verified both experimentally by several groups 6,[20][21][22] and numerically by our previous work. 16 We also need to reiterate that the interpretation of syngas production by way of methane partial oxidation is inappropriate anywhere within the anode, as shown by the discussions about the three-layer structure.…”
Section: Cmm = 2wgs + 4cmh + Mdr ͓13͔mentioning
confidence: 55%